Death at Noon - Morelli, Valentina (Saga Egmont, 2022)
Benvenuto a Santa Caterina - a picturesque Tuscan village where the bells of the local Abbey chime loudly across the idyllic green hillsides. But today, at noon, Sister Isabella notices an eerie quiet; the bells are silent. Puzzled, Isabella makes a horrific discovery: Sister Raffaella is lying lifeless in the cloister! Though it appears she fell from the belfry, a cryptic number etched in the dust near her body suggests otherwise... While Mother Superior is insisting that it's an accident, Isabella isn't convinced. Together with the young Carabiniere Matteo, Isabella begins an investigation of her own and soon uncovers a dark secret... now only divine intervention can help! Monastery, murder and dolce vita - a crime series like a holiday under the Italian sun. Fans of Richard Osman's "Thursday Murder Club" will love this humorous cosy crime read. An intrepid nun makes it her life's work to solve crimes, large and small, that are committed in a picturesque Tuscan village, Santa Caterina. Carabiniere Matteo is happy for this heavenly help, because as Santa Caterina's only policeman, he certainly has his hands full! Valentina Morelli is a German author. With the Sister Isabella Series, she pays homage to her spiritual homeland, and captures the unique feel of life in Tuscany. For her, murder mysteries are a way of telling human stories.